A fast and easy one-step purification strategy for plant-made antibodies using Protein A magnetic beads - Faye, Loïc; Grünwald-Gruber, Clemens; Vezina, Louis-Philippe; Gomord, Véronique; Morel, Bertrand (Frontiers in Plant Science, 2024)
A major difficulty to reach commercial scale production for plant-made antibodies is the complexity and cost of their purification from plant extracts. Here, using Protein A magnetic beads, two monoclonal antibodies are purified in a one-step procedure directly from non-clarified crude plant extracts. This technique provides significant savings in terms of resources, operation time and equipment.